Systematic Evaluation of Neurotoxicity in Children and Young Adults Undergoing CD22 Chimeric Antigen Receptor T-Cell Therapy. Issue 7 (September 2018) - Shalabi, Haneen; Wolters, Pamela L.; Martin, Staci; Toledo-Tamula, Mary Anne; Roderick, Marie Claire; Struemph, Kari; Kane, Eli; Yates, Bonnie; Delbrook, Cindy; Mackall, Crystal L.; Lee, Daniel W.; Fry, Terry J.; et al.
Abstract : Neurotoxicity associated with CAR-T cell therapy can be life-threatening. With rapid development of CAR-T therapies, a systematic method is needed to identify and monitor symptoms of neurotoxicity, elucidate potential etiologies, and compare toxicity across trials. This paper presents a systematic evaluation developed and used to prospectively assess neurotoxicity in our phase I anti-CD22 CAR-T-cell trial and describes the symptoms of neurotoxicity identified using this methodology. Central nervous system (CNS) studies included routine lumbar punctures performed for disease evaluation pretherapy and posttherapy and a baseline brain MRI. Brief cognitive evaluations, assessing 4 domains (attention, working memory, cognitive flexibility, and processing speed), were administered preinfusion and postinfusion. A newly developed CAR-T-specific neurological symptom checklist (NSC) was completed by caregivers at 3 designated time-points. Serial serum cytokine levels were compared with neurotoxicity symptoms and severity. The majority of the first 22 consecutively treated subjects (ages, 7–30) demonstrated stable or improved cognitive test scores following therapy and no irreversible neurotoxicity, despite CAR-T-related antileukemic response, cytokine release syndrome, and trafficking of CAR-T cells to the CSF. The NSC allowed us to document the type and timing of symptoms and explore the etiology of neurotoxicity associated with CD22 CAR-T therapy. Cytokine profiling demonstrated that more concerning symptoms of neurotoxicity, such as hallucination and disorientation, were significantly associated with higher serum cytokine levels, supporting the hypothesis of inflammation-driven neurotoxicity. Systematic assessments of neurotoxicity were feasible in acutely ill children and young adults and served to characterize and monitor the symptoms associated with CAR-T therapy. We recommend these evaluations be incorporated into future immunotherapy protocols.